2010
DOI: 10.4314/jgsa.v12i2.62811
|View full text |Cite
|
Sign up to set email alerts
|

New Sources of Resistance in Cowpea to the Cowpea Aphid (Aphis Craccivora Koch) (Homoptera: Aphididae)

Abstract: Twenty-two advanced breeding genotypes of cowpea were evaluated for their responses to infestation by the cowpea aphid, Aphis craccivora Koch. The aim of the study was to identify genotype(s) of cowpea resistant to A. craccivora to be used as breeding line(s). Seedling screening technique and aphid growth and reproduction on each genotype were used to classify the genotypes into resistant and susceptible groups. The cowpea genotypes SARC 1-57-2 and SARC 1-91-1 were found to be the most resistant genotypes, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…These results are consistent with those of Kusi et al (2010) who identified SARC-1-57-2 and SARC1-91-1 as resistant to aphids. IT97K-556-6 is the most resistant line to all the three strains of aphids with an average survival rate equal to 93.33% and a degree of infestation equal to 1.4.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These results are consistent with those of Kusi et al (2010) who identified SARC-1-57-2 and SARC1-91-1 as resistant to aphids. IT97K-556-6 is the most resistant line to all the three strains of aphids with an average survival rate equal to 93.33% and a degree of infestation equal to 1.4.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, in this study the confinement of aphids increased the parasitic pressure on plants. This pressure would have been able to induce an excessive compensatory response (Kusi, 2010) in KN1 physiological response, which was manifested by a much greater production of leaves. This compensatory response, combined with the antibiosis activity developed by the line, gave it an unexpected resistance to aphids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SARC 1‐57‐2 was observed to be resistant to A. craccivora under both screen‐house and field conditions among a large number of test lines (Kusi et al., ). One hundred and sixty‐nine (169) F 2 lines of the cross between ‘Apagbaala’ and SARC 1‐57‐2 were tested for their reaction to aphid infestation in a screen‐house facility using standard protocols (Bata et al., ; Kusi et al., ). As soon as individual lines could be unambiguously classified into resistant or susceptible classes, they were sprayed with lambda cyhalothrin (Lambda Super ® ) to control the aphids.…”
Section: Methodsmentioning
confidence: 99%
“…Ongoing research at the CSIR‐Savanna Agricultural Research Institute (CSIR‐SARI) to identify additional sources of aphid resistance in cowpea revealed a number of advanced breeding lines, including SARC 1‐57‐2, with high levels of resistance (Kusi et al., ). In these tests, lines with the IT84S‐2246 source of resistance were not more resistant than the susceptible check, ‘Apagbaala’.…”
Section: Introductionmentioning
confidence: 99%